Pandemic or “Plandemic”?: The Mediating Role of Epistemic Justification Strategies in the Relationship Between COVID‐19 Conspiracy Beliefs and COVID‐19 Vaccine Conspiracy Beliefs - Ali Gökalp; Servet Üztemur; Po‐Ching Huang; Aslı Kartol; Hsin‐Chi Tsai; Erkan Dinç; Mark D. Griffiths; Chung‐Ying Lin (Brain and Behavior)
ABSTRACT Background In today's post‐truth times, where personal feelings and beliefs have become increasingly important, determining what is accurate knowledge has become an important skill. This is especially important during uncertainty crises (e.g., epidemics and pandemics) because alternative explanations other than scientific knowledge may be disseminated vigorously. Epistemic justification concerns how and in what way the truth of knowledge claims is justified and the criteria for knowledge to be true and/or a fact. Given this backdrop, the present study examined how individuals reacted to conspiracies in an uncertainty crisis (using the COVID‐19 pandemic as an example). Aim The mediating role of epistemic justification was investigated regarding its relationship between COVID‐19 conspiracy beliefs and COVID‐19 vaccine conspiracy beliefs. Methods A cross‐sectional study was conducted incorporating a multifactorial correlational design. Using convenience sampling, 690 participants (55.7% females, Mage = 32.24 years, SD = 9.75) from different regions of Türkiye completed an online survey via Google Forms. Results The results demonstrated a strong and statistically significant correlation between beliefs in COVID‐19 conspiracy theories and beliefs in COVID‐19 vaccination conspiracy theories. The mediating effects of justification by authority and personal justification were statistically significant between COVID‐19 conspiracy beliefs and COVID‐19 vaccine conspiracy theories. Conclusion Using the COVID‐19 pandemic as an example, the present results indicated the complex relationships between conspiracy beliefs and epistemic justification. The present results indicate the importance of authorities in taking early action to provide scientific evidence and information to the public to avoid individuals believing false information.